1993
DOI: 10.1090/s0002-9939-1993-1143013-3
|View full text |Cite
|
Sign up to set email alerts
|

On the nonautonomous Volterra-Lotka competition equations

Abstract: Abstract. A nonautonomous competitive Lotka-Volterra system of two equations is considered. It is shown that if the coefficients are continuous and satisfy certain inequalities, then any solution that is positive at some point has the property that one of its components vanishes while the other approaches a certain solution of the logistic equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(91 citation statements)
references
References 8 publications
1
87
0
Order By: Relevance
“…Montes de Oca and Zeeman [8,Lemma 3.1]). We also notice that these ideas, especially (1.2), are extended to nonautonomous (see [7,8], Ahmad [1], Ahmad and Lazer [3]) and retarded autonomous ( [5] and [4, §4.1- §4.3]) systems. No doubt the popularity of (1.2) is attributed to its conciseness.…”
Section: Zhanyuan Houmentioning
confidence: 98%
“…Montes de Oca and Zeeman [8,Lemma 3.1]). We also notice that these ideas, especially (1.2), are extended to nonautonomous (see [7,8], Ahmad [1], Ahmad and Lazer [3]) and retarded autonomous ( [5] and [4, §4.1- §4.3]) systems. No doubt the popularity of (1.2) is attributed to its conciseness.…”
Section: Zhanyuan Houmentioning
confidence: 98%
“…For example, persistence and extinction of (1.1) were considered in [1,2,35,37]. Zhao et al [38] investigated permanence and global attractivity of model (1.1).…”
Section: Introductionmentioning
confidence: 99%
“…supremum) of the function g, then system (LV) is persistent and globally attractive. To be more precise, Gopalsamy proved that in the almost periodic case the conditions (GAT) In [1] and [4] a nonautonomous logistic equation (L) u 0 (t) = u 0 (t)(a(t) − b(t)u 0 (t)), t ∈ R, is considered. It is well known that an autonomous logistic equation…”
mentioning
confidence: 99%
“…Ahmad [1] and Coleman [4] showed that in the nonautonomous equation (L) the role of the globally attracting carrying capacity of the autonomous equation is played by a well defined canonical solution u * i (t) to which all other solutions converge.…”
mentioning
confidence: 99%
See 1 more Smart Citation